L’effectivité de la protection des personnes par le droit des données à caractère personnel - Vergnolle, Suzanne (Université Paris 2, 2020)
Généralement présenté comme une matière réservée aux initiés, le droit des données à caractère personnel intéresse pourtant le plus grand nombre. Les technologies de l’information sont si répandues que les menaces liées à leurs usages pèsent sur tous. L’effectivité de la protection des personnes se révèle être l’enjeu majeur de ce droit. Pour endiguer les risques d’atteinte aux personnes, le domaine des données à caractère personnel s’est étendu. Pouvons-nous considérer que cette expansion, façonnée au fil des interprétations et modifications législatives, débouche sur une meilleure protection des personnes ? Cela n’est pas certain. Pour parvenir à cette fin, il a été jugé opportun d’encadrer la notion de donnée à caractère personnel. Cette qualification doit être limitée aux données directement identifiantes et aux données indirectement identifiantes dont le traitement induit un lien avec une personne physique. Cette approche a appelé un renforcement du régime juridique associé. Les règles actuelles de cette matière, bien que nombreuses et enchevêtrées, sont favorables à la mise en œuvre des traitements et les atteintes à la liberté d’autodétermination sont peu encadrées. Afin de prévenir les risques d’atteinte aux personnes, un raffermissement de certains principes a été proposé. C’est surtout une meilleure mise en œuvre de ce droit qu’il a fallu garantir. Celle-ci passe par une intensification et une diversification des contrôles. Elle se matérialise surtout par une amélioration de la réalisation juridictionnelle du droit des données à caractère personnel, qui doit reconnaître aux personnes des moyens effectifs pour agir et défendre leurs données.
Keywords: CNIL; Commission nationale de l’informatique et des libertés; Digital law; Données à caractère personnel; Droit du numérique; Droit à la vie privée; Droits de la personnalité; France; Freedom; GDPR; General Data Protection Regulation; Liberté; Personal data; Personality rights; Privacy; Protection de l'information (informatique) – Droit – France; Protection des personnes; Protection of individuals’ rights; RGPD; Règlement général sur la protection des Données; Vie privée

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework